Biomacromolecule assembly based on gum kondagogu-sodium alginate composites and their expediency in flexible packaging films - Ramakrishnan, Rohith K; Wacławek, Stanisław; Černík, Miroslav; Padil, Vinod V T (International journal of biological macromolecules, 2021)
The assembly of bio-based macromolecules of gum kondagogu/sodium alginate (KO/SA) was fabricated using glycerol as a plasticiser and their optimum blending ratio was identified based on their physical and chemical, structural, mechanical, barrier, and morphological properties. The attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) analysis show that both biomacromolecules are well organised due to the hydrogen bond interaction between molecular chains involving the hydroxyl, carbonyl, and acetyl groups. Structural identification was performed by recording X-ray diffraction (XRD) spectra. Field emission scanning electron microscopy (FESEM) was used to identify the distinction between the surface of the films of biopolymers, and their conjugates, where the addition of SA increased the surface homogeneity and smoothness. The water contact angle of the blend films reached up to 81°, although the value for pure biomacromolecule films was very low. The blend films also exhibited high tensile strength (up to 24 MPa) compared to the pure biopolymer films. Investigation of film-forming ability, mechanical strength, permeability, transparency, and biodegradability of the developed KO/SA bio-macromolecular association may be established as green and sustainable food packaging films.
Keywords: rostlinné gumy; Gum kondagogu/alginate composite film; membrány umělé; algináty; Membranes, Artificial; Alginates; Food packaging; obaly potravin; Food Packaging; Plant Gums; Biodegradation; Bixaceae